Analysis of the Local Wisdom of Batu Urip in Lubuklinggau City in Ecological and Historical Context - Agus Susilo; Yohana Satinem; Sarkowi (Postgraduate, University of Mataram, 2024)
This research explores the relationship between historical and ecological aspects in Batu Urip Village, Lubuklinggau City. Batu Urip, as a historical and cultural area, holds various important heritage sites such as traditional houses and ancestral graves, reflecting the richness of local culture. Ecologically, Batu Urip's physical environment, including forests and rivers, influences the community's way of life as well as traditional agricultural methods and building materials. The study highlights the importance of integrating ecosystem conservation with cultural heritage preservation. Conservation activities must consider environmental impacts to maintain ecological balance and protect historical sites. Additionally, education on local wisdom values and environmental preservation should be incorporated into school curricula to raise awareness among the younger generation. The research also emphasizes the need for collaboration between communities, government, and educational institutions to support the preservation of Batu Urip amidst the challenges of globalization and digitalization. Through a holistic approach, Batu Urip can maintain its historical identity while ensuring the sustainability of its local ecosystem, making it a wise and exemplary city at both regional and national levels.